PURIFICATION AND CHARACTERIZATION OF HYPERTHERMOSTABLE RECOMBINANT Pyrococcus furiosus ?-AMYLASE EXPRESSED IN Pichia pastoris KM71 - Delfahedah, Yulia
?-Amylase (EC 3.2.1.1) hydrolyzes ?-1,4-glycosidic bond in starch producing linear and branch oligosaccharides. In starch processing industry, thermostable ?- amylase was generally used to convert starch into oligosaccharides. Hyperthermostable Pyrococcus furiosus ?-amylase (PFA) has an activity at high temperature. The aims of this study were to purify and characterize the hyperthermostable recombinant PFA expressed in Pichia pastoris KM71. This research was conducted into several stages, namely transformation of P. pastoris KM71 with pPICZ?A-PFA, optimization of incubation time and concentration of methanol for production of PFA, purification of PFA by Co-NTA affinit y chromatography under denaturing condition, and characterization of purified PFA.